Hematological profile of goats fed Mimosa caesalpinifolia and infected with gastrointestinal nematodes (Research, Society and Development, 2022)
The aim of this research was to evaluate the hematological response of goats submitted to treatment with Condensed Tannin from thrush (Mimosa caesalpinifolia) on gastrointestinal nematodes. Blood samples from 24 crossbred Boer goats, naturally infected and raised in confinement, were divided into four groups of six, namely: Group I: treated with Condensed Tannin (TC); Group II: treated with TC by adding Polyethylene Glycol (TC+PEG); Group III: positive control, treated with monepantel (5mg Kg-1/PV) and Group IV: negative control, no treatment. It was observed that only the group treated with monepantel showed a significant reduction in egg counts per gram of feces, with satisfactory post-treatment results throughout the study period. For the erythrocyte variable, with the exception of the untreated group, expected values ​​were found for goats. The mean values ​​for mean globular volume (VGM) increased significantly in all groups evaluated, rising at times above the reference values ​​established for the goat species (16 – 25fL) and the parameterMean Globular Hemoglobin Concentration (CHGM) showed large variations between the groups studied. Changes of clinical importance were observed in the white blood cell count, among the different groups studied, with counts below the reference values ​​for the goat species for the parameters: segmented, lymphocytes and eosinophils. It is concluded that the alterations found in the hematological data of goats showed slight differences between the groups treated with TC and TC+PEG when compared to the negative group.